Kajian Ilmiah Infrastruktur Transportasi terhadap Konsumsi Energi dan Dampaknya terhadap Pertumbuhan Ekonomi di Provinsi Aceh - Teuku Faiz Kamal; Muhammad Irfan (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the impact of transportation infrastructure on energy consumption and its effect on economic growth in Aceh Province using an infrastructure science approach. Using panel data from 2010 to 2022, the study analyzes the influence of electricity customers per capita, provincial road length in good condition, total road length, real gross fixed capital formation per capita, average years of schooling, government consumption share to real GRDP, and the agricultural sector’s GRDP share. The findings reveal that electricity customers per capita, total road length per capita, and average years of schooling have a positive and significant impact on economic growth. In contrast, provincial road length in good condition has a negative and insignificant effect, while real gross fixed capital formation per capita shows a positive but insignificant impact. Meanwhile, government consumption share and the agricultural sector’s contribution to GRDP negatively and significantly affect economic growth.